Strategy of immigration office Class 1 Batam in reducing passport abuse by the prospective Indonesian labor in nonprocedural - Lestari, Linayati; Hanafi, Hanafi; Solihin, Muhammad; Johar, Siti Sarawati; Ani, Fauziah (2020)
The existence of nonprocedural Indonesian Workers who work abroad in a weak position, because they do not have legal status or there is no legal regulation that protects their workforce. Non-procedural TKI are those who do not have a work contract, work visa / permit, insurance and labor documents. Non-procedural TKI go to work abroad only using an ordinary passport, the passport used for visits. This study aims to find out what are the strategies and how the implementation of the Batam Special Class 1 Immigration Office strategy policy in reducing passport abuse by prospective non-procedural Indonesian workers. The research results are described by theory in the strategic dimension according to James Brian Quinn, namely, the objectives, policies and programs that will produce a strategy. The results showed the strategy carried out by the Batam Special Class 1 Immigration Office was to tighten the issuance of passports by conducting careful and selective checks on the correctness of formal and material requirements. Office policy Immigration, namely prospective Indonesian Workers will be asked to attach a passport application recommendation letter issued by the Manpower Office, and the Class 1 Special Batam Immigration Office program through the provision of passport making services using the One Stop Service System to reduce passport abuse by prospective Indonesian Workers Nonprocedural.